Scriptwriting - Ricky Telg (EDIS, 2012)
For video productions, not only does the script have to read well for the eye, but it also has to sound good for the ear. This 3-page fact sheet provides an overview of good scriptwriting techniques. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, June 2012.